Language, labor and reification - McGill, Kenneth (Language Sciences, 2020)
In this article, I attempt to describe how language is reified, using the call center as an extended example. I take up recent debates regarding language and economic value, attempting to disentangle a by now substantial series of arguments about language and commodification. The theoretical core of the paper is drawn from the work of Georg Lukács, who provided the account of reification that was at the root of twentieth century critical theory. Following Lukács, I argue that what is indispensable in the process of reification is both a “contemplative stance” in relation to economic laws and the presence of “special partial systems” within the production process of commodities. These are particularly important considerations for what I refer to as the one-sided rationalization of language that occurs in call centers in particular, but also on a more widespread social basis. © 2020 Elsevier Ltd
Keywords: Commodity; Consciousness; Economic value; Language; Reification; dept.ant; peer-reviewed